Strategy for Handling Stunting Through the First Thousand Days of Life for Mothers and Babies in Kaleke Village, West Dolo District, Sigi Regency - Ahmad Yani; Sudirman; Corina Pagalla (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
National Strategy for accelerating the prevention of stunting is a reference document that can be used to ensure convergent coordination of all interventions for all stakeholders in supporting the Indonesian Government's commitment. Kaleke Village is the working area of the Kaleke Community Health Center with the highest incidence of stunting compared to other villages. The incidence of stunting in 2020 out of 105 toddlers suffering from stunting was 37 ( 35.23 %). The number of stunting incidents in 2021 is 25 incidents with a percentage of 28.74% of the total 101 incidents in the Kaleke Community Health Center Working Area. The purpose of this study was to determine the strategy through the first thousand days of life for mothers and babies in Kaleke Village, Dolo Barat District, Sigi Regency This research is a qualitative research to find out strategies for handling stunting through the first thousand days of life for mothers and babies in Kaleke Village, West Dolo District, Sigi Regency through observation, in-depth interviews and documentation . The research results show that the strategy for handling stunting through the first thousand days of life for mothers and babies in Kaleke Village, West Dolo District, Sigi Regency is carried out by providing counseling to mothers, providing additional food, distributing biscuits, providing vitamins for young women . The strategy for handling stunting through the first thousand days of life for mothers and babies in Kaleke Village, West Dolo District, Sigi Regency is carried out by providing counseling to mothers, providing additional food, distributing biscuits, providing vitamins for young women . It is recommended that the Kaleke Community Health Center improve services to pregnant women, infant mothers and mothers of toddlers in handling the problem of stunting through the first 1000 days of life proactively on a door-to-door basis.